Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

-2x2 – 3x + 1 for x = -3


Sagot :

Answer:

[tex]-8[/tex]

Step-by-step explanation:

[tex]-2\left(-3\right)^2-3\left(-3\right)+1[/tex]

[tex](-3)^{2} =9[/tex]

[tex]=-2\times 9-(3)+1[/tex]

[tex]-2\times9=-18[/tex]

[tex]=-18-3\left(-3\right)+1[/tex]

[tex]3(-3)=-9[/tex]

[tex]=-18-\left(-9\right)+1[/tex]

[tex]=-8[/tex]